VIOLATION OF THE BODY IN ALGERIAN NOVEL COLONEL OF ZBARBAR AS AN EXAMPLE - Dr. KAREEM AJEEL SAHI (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The novel Colonel Zbarbar is like a self-biography written by (Moulay Urban) , as one officer ’s army which national silk during the liberation war , boldly high , after leaving the army and the population POLICY reveals p of the unseen French occupation of the facts , concerning the method of dealing with human Algerian to force him to accept, exposed by this population liras , violations diversifies methods, a way that does not differentiate between Waller Gaal and Allen worsened, but deals with Allen Worsened in the strongest corporal punishment in order to force Waller majority of the Algerian rebels to give up its principles , which arose from it, Verdr dignity rooms at times, and in front of creation at other times , The body was a French means the colonial extent exerted pressure on the Algerians through violating sexually without the distinction between the sexes or violation noses, fingers, feet, or poured Wales at the protector on the bodies or throw it from places of high - rise ... etc., so we tried through this research stand on those methods practiced on days of the revolution through the Algerian shed vulnerable light of these Alanth physical Akat of different kinds, and noted that the vision that formed a pattern constructivist linked to consciously the author of this novel and the awareness of the society in which they expressed.